Z-scheme BaFe2O4/BiOCl heterojunction composites for photocatalytic palm oil mill effluent degradation and bacteria inactivation - Tan, Jin Han (2024)
In recent years, organic pollution and biological hazards have become indisputable considerable environmental issues. Such as a raising POME production led by the surging demand and supply of palm oil. Semiconductor-based photocatalysis has been regarded as a promising and sustainable solution in minimizing the negative impacts of these matters. Therefore, a two-step precipitation-hydrothermal method was employed to fabricate novel Z-scheme BaFe2O4/BiOCl composites as efficient visible light-driven photocatalysts. The physicochemical properties and morphological characteristics of the fabricated composites were investigated via XRD, FTIR, FESEM, EDX, TEM, XPS, VSM, UV-vis DRS, Mott-Schottky, TPR, EIS and specific surface area characterization methods. The XRD spectra shown BiOCl as tetragonal structure, while additional diffraction peak is from the orthorhombic structure of BaFe2O4 in the composite. While the FTIR spectra of BaFe2O4/BiOCl composite, it demonstrated that the characteristic peaks of BaFe2O4 and BiOCl occurs simultaneously. The FESEM displayed that the 5 wt% BaFe2O4/BiOCl shows the aggregated BaFe2O4 particles cover the surface of sheet structure BiOCl to form a tightly contacted heterostructure while EDX analysis confirmed the successful synthesis of 5 wt% BaFe2O4/BiOCl composite. Whereas the TEM images displayed the lattice fringes in the 5 wt% BaFe2O4/BiOCl corresponded to the (110) plane of BiOCl and the (212) plane of BaFe2O4, with spacings of 0.275 nm and 0.334 nm, respectively. In addition, the XPS findings further validated the coexistence of BiOCl and BaFe2O4 within composite, agreeing well with the XRD, FTIR and EDX findings. Via a VSM analysis, the composite demonstrated a symmetrical S-shaped of magnetization curve, revealing the ferromagnetic behavior of the 5 wt% BaFe2O4/BiOCl. The BiOCl nanosheets loaded with 5 wt% BaFe2O4 particles (5 wt% BaFe2O4/BiOCl) demonstrated the best visible light photoactivity with a palm oil mill effluent (POME) decomposition efficiency of 61% within 210 min. The photocatalytic enhancement benefited from the creation of Z-scheme heterojunction coupling BaFe2O4 with BiOCl, hence accelerating the interfacial charge transfer and maintaining strong redox potential for active radical generation. We also studied the operating parameter such as photocatalyst loading, solution pH and initial POME concentration and the optimum parameter discovered is 0.5 g/L of photocatalyst loading, 50 ppm of POME and solution pH of 2. Moreover, by regulating the pH value of photoreaction system, more superior POME degradation efficiency was attained and reached 85% at the same duration. With the assist of H2O2, the POME decomposition was greatly improved and reached 98% with a rate constant of 0.222 min-1 in the same duration. Interestingly, the 5 wt% BaFe2O4/BiOCl composite also possessed a convenient catalyst separation along with good recyclability with only 7% loss in efficiency after four successive runs. Additionally, the band structure of 5 wt% BaFe2O4/BiOCl was evaluated using UV-vis DRS, and Mott-schottky analysis. The TPR and EIS shown that the 5 wt% BaFe2O4/BiOCl with enhanced separation of photoexcited carriers. Based on the active species scavenging experiment, superoxide radical was found as the eminent active species during the POME treatment. On the other hand, we used the Langmuir-Hinshelwood model to study the kinetics of photocatalytic degradation of POME over the as-synthesized products, finding that the photocatalytic reactions of POME conformed to the pseudo-first-order kinetics of Langmuir-Hinshelwood model, with the highest apparent rate constant determined to be 0.0222 corresponding to 3 mmol/L of H2O2 concentration. In addition, the electrical energy consumption per order was determined with value of 54.54 kWh/m3 order with the operation cost of RM 23.83 per m3 order. Phytotoxicity tests showed that the POME exhibited reduced phytotoxicity from 85% to 78% after undergoing photodecomposition, with longer radical length observed than before degradation. In addition to the investigation of POME treatment, the fabricated 5 wt% BaFe2O4/BiOCl composite was also successfully employed to inactivate the E. coli and B. cereus. This study revealed that the as-fabricated BaFe2O4/BiOCl composite had great potential applications to degrade various organics and to inactivate bacteria from wastewater.